ENVIRONMENTAL EXPOSURE AND PSYCHOLOGICAL DISTRESS AMONG UNIVERSITY STUDENTS LIVING IN AN INDUSTRIAL AREA - Septiansyah, Dhimas Anggi; Rohmawati, Nina Rizka (Jurnal Mitra Kesehatan, 2026)
Introduction : Psychological distress among university students remains a significant mental health concern, and environmental exposure is one of the contributing factors to this condition. This study aimed to analyze the relationship between environmental exposure and psychological distress among students in an industrial area. Method: This study employed an analytical observational design with a cross-sectional approach conducted at Politeknik Kesehatan Kerta Cendekia from August 2025 to March 2026. The sample consisted of 105 students who agreed to participate in the study. Data were collected using an environmental exposure questionnaire developed by the researchers and the DASS-21 questionnaire to assess psychological distress, which includes three indicators: stress, anxiety, and depression. Data were analyzed using SPSS with the Spearman Rank Correlation test. Result: The results showed a positive relationship between environmental exposure and psychological distress, with p-values of 0.047 for the stress indicator, 0.006 for the anxiety indicator, and 0.026 for the depression indicator. Conclusion: This study concludes that there is a  positive relationship between environmental exposure and psychological distress among students in industrial areas. Educational institutions and the government need to collaborate on promotive and preventive efforts to minimize the impact of environmental exposure on students’ psychological distress